Information Cascades in the Laboratory - Anderson, Lisa R.; Holt, Charles A. (American Economic Review, 1997)
When a series of individuals with private information announce public predictions, initial conformity can create an "information cascade" in which later predictions match the early announcements. This paper reports an experiment in which private signals are draws from an unobserved urn. Subjects make predictions in sequence and are paid if they correctly guess which of two urns was used for the draws. If initial decisions coincide, then it is rational for subsequent decision makers to follow the established pattern, regardless of their private information. Rational cascades formed in most periods in which such an imbalance occurred. In many economic situations, agents observe private signals of some underlying state and make public decisions. Subsequent decision makers face a dilemma if their own private signal is indicative of a state that is unlikely given the previously observed decisions. An "information cascade" occurs when initial decisions coincide in a way that it is optimal for each of the subsequent individuals to ignore their private signals and follow the established pattern. For example, suppose that a worker is not hired by several potential employers because of poor interview performances. Knowing this, an employer approached subsequently may not hire the worker even if the employer's own assessment is favorable, since this information may be dominated by the unfavorable signals inferred from previous rejections.